Robbery in the illegal drugs trade : violence and vengeance - McLean, Robert; Densley, James A. (James Andrew), 1982- (Bristol shorts research., 2022)
Uniquely focusing on robberies involving drug dealers and users, this book considers the material and emotional gains and losses to offenders and victims, and offers policy recommendations to reduce occurrences of this common crime.